2001
DOI: 10.1038/sj.bjp.0704319
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular distribution of psychotropic drugs in the grey and white matter of the brain: the role of lysosomal trapping

Abstract: 1 Since the brain is not a homogenous organ (i.e. the phospholipid pattern and density of lysosomes may vary in its dierent regions), in the present study we examined the uptake of psychotropic drugs by vertically cut slices of whole brain, grey (cerebral cortex) and white (corpus callosum, internal capsule) matter of the brain and by neuronal and astroglial cell cultures. 2 Moreover, we assessed the contribution of lysosomal trapping to total drug uptake (total uptake=lysosomal trapping+phospholipid binding) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…The weaker signal in the GS2 tumor versus the healthy brain as well as the higher variability in distribution within the tumor compared with the U87 tumor may be explained by differences in tumor vascularization, which could impact GNE-317 distribution. Images suggest also different compound levels in white versus gray matter as previously reported with brain penetrant compounds (Daniel et al, 2001;Li et al, 2009).…”
Section: Resultsmentioning
confidence: 48%
“…The weaker signal in the GS2 tumor versus the healthy brain as well as the higher variability in distribution within the tumor compared with the U87 tumor may be explained by differences in tumor vascularization, which could impact GNE-317 distribution. Images suggest also different compound levels in white versus gray matter as previously reported with brain penetrant compounds (Daniel et al, 2001;Li et al, 2009).…”
Section: Resultsmentioning
confidence: 48%
“…Monensin is routinely used in the cattle and a Vesicular to cytosolic concentration ratio ϭ (1 ϩ 10 pKa Ϫ pHv)/(1 ϩ 10 pKa Ϫ pHi) (Myers et al, 1995), where pHi Ϸ 7.27 is the assumed cytosolic pH (Le Couteur et al, 1993), pHv Ϸ 4.4 is the assumed lysosomal pH (Daniel et al, 2001) and pHv Ϸ 6.67 is the assumed mitochondrial pH in the fasted state (Pietri et al, 2001).…”
Section: Hepatic Disposition Of Basic Drugs 233mentioning
confidence: 99%
“…A potential consequence of an apparent irreversible sequestration of basic drugs into acidic vesicles is a potentially reduced drug bioavailability (de Duve et al, 1974;Ohkuma and Poole, 1978) or drug interactions (Daniel and Wojcikowski, 1999b;Nebbia et al, 1999). Lysosomal trapping of basic lipophilic drugs has also been demonstrated to be an important determinant of disposition for desipramine and chloroquine and psychotropic compounds such as the piperidine and piperazine-type neuroleptics (Daniel et al, 2001). The lysosomotropic properties of basic drugs are particularly important determining drug disposition and pharmacokinetics in lysosome-rich organs such as lungs, kidneys, or the liver.…”
mentioning
confidence: 99%
“…This compound (Na + /H + -ionophore) is commonly recognized as fast and efficient lysosomal inhibitor [17,18]. We have suggested that ammonium chloride reduces the high lipophilicity of CPZ and prevents deterioration NMDAR functions.…”
Section: Discussionmentioning
confidence: 99%
“…This compound (Na + /H + -ionophore) is commonly recognized as fast and efficient lysosomal inhibitor [18]. Lysosomal trapping is an important mechanism of cellular and body distribution of basic psychotropic drugs, such as phenothiazine neuroleptics [19].…”
Section: Discussionmentioning
confidence: 99%